Problematics in the Case of Bribery of State Officials in the Case of Illegal Mining (Ismail Bolong) - Vicki Dwi Purnomo (Jurnal Multidisiplin Madani, 2022)
There are many definitions of unlawful acts, some call unlawful acts as violations of the law, as acts that violate the rights of others.  The purpose of the research conducted was to solve the problem of bribery cases of state officials in illegal mining cases. The research method used is The research approach that researchers use is the Legal-Live Case Study approach.  The results of the research conducted were based on the author's research in the field, Ismail Bolon's statement stated that he was a coal miner in Malangayu District, Kutai Katanegara (Kuka) Regency because he admitted his own actions as a coal collector and was suspected of bribing a police officer. This happened because of the weak enforcement of Article 158 of Law Number 4 of 2009 concerning Mineral and Coal Mining.  Based on the author's research in the field, Ismail Bolon's statement stated that he was a coal miner in Malangayu District, Kutai Katanegara (Kuka) Regency, for admitting his own actions as a coal collector and allegedly bribing a police officer. This happened because of the weak enforcement of Article 158 of Law Number 4 of 2009 concerning Mineral and Coal Mining.  The conclusion of the research conducted by the monitoring of the illegal mining process in the East Kalimantan region is still weak considering that there are dozens or even hundreds of illegal mines operating and it is suspected that there are law enforcement personnel who own this business and are involved